Confronting Cultural Barriers in Public Speaking through Multiple Learning Strategies: A Case of Indonesian EFL Learners - Concilianus Laos Mbato (Humaniora, 2020)
Cultural barriers, anxiety and lack of English competence may lead to EFL students’ failures in public peaking. Conducive learning environments, right coaching and learning strategies are likely to increase the possibility of students’ success. This research aimed to investigate whether the implementation of multiple learning strategies empowered Indonesian EFL students’ public speaking skills. 56 students enrolled in three public speaking classes of Sanata Dharma University, Yogyakarta in the academic year 2017-2018 participated in the research. One overriding research question was postulated, i.e., to what extent does the implementation of multiple learning strategies empower students’ public speaking skills? To answer the question, classroom mixed-methods research was employed where students filled out four different questionnaires and submitted focus group discussion (FGD) results at the end of the semester. Quantitative and qualitative data analyses indicated that students had very high perceptions about the use of and the combinations of reflections, peer-, teacher-, and self-assessments, independent learning plans and activities. They believed that multiple learning strategies implemented in the Public Speaking Class enabled them to be independent, responsible, and better learners. They also acknowledged becoming more confident and better public speakers. This study contributes to the body of knowledge in public speaking in two important ways. First, learning to speak in public for non-native speakers of English should begin with raising their awareness about cultural barriers that might inhibit the development of the necessary skills in public speaking. Second, teaching public speaking to EFL students requires the adoption of multiple learning strategies including strategies to confront imminent cultural barriers. This research, therefore, urges public speaking trainers and teachers in EFL settings to include intercultural understanding and multiple learning strategies in their public speaking classes in order to empower students’ public speaking skills